INFLUENCE OF EARNING PER SHARE (EPS), PRICE TO BOOK VALUE (PBV) AND NET PROFIT MARGIN (NPM). ON THE PRICES OF MINING SECTOR SHARES LISTED ON THE IDX 2020 -2023 - Mohammad Adam Roykhani; Syaiful Syaiful (International Journal of Economic Integration and Regional Competitiveness, 2024)
This research discusses the role of the mining sector in driving Indonesia's economic growth. The mining sector makes a major contribution to exports and government income. Investment in the mining sector is an alternative choice for people to manage and plan their finances. Share prices in the capital market are very important because they reflect the issuer's achievements. This research uses financial ratios such as Net Profit Margin (NPM), Earning per Share (EPS), and Price to Book Value (PBV) as dependent variables, and share price as an independent variable. The aim of this research is to understand how Earning Per Share (EPS), Net Profit Margin (NPM), and Price Book Value (PBV) influence share prices in mining companies listed on the IDX from 2020 to 2023. The results of this research are expected to contribute to theory and practice in developing effective financial strategies to increase fair prices shares in mining companies in Indonesia.